Fitness benefits from co-display favour subdominant male–male partnerships between phenotypes. (March 2023) - Tolliver, James D.M.; Kupán, Krisztina; Lank, David B.; Schindler, Susanne; Küpper, Clemens
Abstract : Male–male competition over matings is a key driving force in the evolution of courtship. Typically, male–male competition is an individual affair selecting for dominance and aggression. Yet, some males forgo direct confrontation improving their reproductive success through cooperation. Occasionally, this leads to specialized alternative reproductive tactics that operate at the intersection of cooperation and conflict. We informed a community game model with empirical data derived from previous studies, to examine cooperation dynamics between lekking male ruffs, Calidris pugnax, using two tactics: resident and satellite. Residents defend display courts against one another on leks of up to seven residents. Nonaggressive satellites forgo court defence and engage in cooperative co-displays with residents. Previous studies suggest such co-displays alter female mate choice, yet the exact magnitude and consequences remain unclear. We modelled the propensity for resident/satellite co-display by examining its influence on male mating success. Male mating success was a function of lek size, resident rank, satellite competitiveness within a co-display and female preference for co-display. We assumed that co-display alters female preference such that copulations are drawn from single display courts to co-display courts proportional to the existing resident mating skew. Under this assumption, all residents benefit from co-display over single display, except for α-residents co-displaying with the most competitive satellites on large leks. Thus, satellites could predominantly choose their preferred co-display partner, but achieved the highest copulation rates with lower-ranking residents on intermediate-sized leks. Co-display between the satellite and lower-ranking residents reduced the resident mating skew. However, satellite copulation rates were similar over a range of co-display partners, meaning that a variety of co-display dyads is possible, which is consistent with observations in nature. We conclude that, given our model assumptions, co-displaying reduces the impact of male dominance on mating success and ultimately alters the course of sexual selection. Highlights: Residents prefer co-display over single display, regardless of their rank. Satellites benefit most when co-displaying with low-ranking residents. Female preference for male-male cooperation may alter the path of sexual selection.